Preface: 2024 IEEE 7th International Conference on Knowledge Innovation and Invention - Teen-Hang Meen; Chun-Yen Chang; Cheng-Fu Yang (Engineering Proceedings, 2025)
This volume presents the proceedings of the 2024 IEEE 7th International Conference on Knowledge Innovation and Invention (IEEE ICKII 2024) [...]